2020
DOI: 10.4196/kjpp.2020.24.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of promyelocytic leukemia/p53 affects signal transducer and activator of transcription-3 activity in response to oncostatin M

Abstract: Promyelocytic leukemia (PML) gene, through alternative splicing of its Cterminal region, generates several PML isoforms that interact with specific partners and perform distinct functions. The PML protein is a tumor suppressor that plays an important role by interacting with various proteins. Herein, we investigated the effect of the PML isoforms on oncostatin M (OSM)-induced signal transducer and activator of transcription-3 (STAT-3) transcriptional activity. PML influenced OSMinduced STAT-3 activity in a cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Although it has been shown that a p53 nonsense mutant can still localize to PML NBs [ 135 ], raising the possibility that other p53 mutants, including the more common p53 missense mutations, also localize to PML NBs, the functional consequences remain largely unexplored. PML has been found to be important for cell proliferation, p53 transactivation [ 136 ], and STAT3 signaling in cancer cells harboring missense p53 mutations [ 137 ]. The interaction of mutant p53 with STAT3 has been shown to increase JAK2/STAT3 signaling, promoting cancer cell proliferation and tumorigenesis [ 138 ].…”
Section: Pml Biocondensates and The P53 Responsementioning
confidence: 99%
“…Although it has been shown that a p53 nonsense mutant can still localize to PML NBs [ 135 ], raising the possibility that other p53 mutants, including the more common p53 missense mutations, also localize to PML NBs, the functional consequences remain largely unexplored. PML has been found to be important for cell proliferation, p53 transactivation [ 136 ], and STAT3 signaling in cancer cells harboring missense p53 mutations [ 137 ]. The interaction of mutant p53 with STAT3 has been shown to increase JAK2/STAT3 signaling, promoting cancer cell proliferation and tumorigenesis [ 138 ].…”
Section: Pml Biocondensates and The P53 Responsementioning
confidence: 99%